2020
DOI: 10.1007/s00262-020-02497-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in the immune system may influence the response to anti-PD1 therapy in metastatic melanoma patients

Abstract: Anti-PD1 treatment has improved the survival of metastatic melanoma patients, yet it is unknown which patients benefit from the treatment. In this exploratory study, we aimed to understand the effects of anti-PD1 therapy on the patients' immune system and discover the characteristics that would result in successful treatment. We collected peripheral blood (PB) samples from 17 immuno-oncology-naïve metastatic melanoma patients before and after 1 and 3 months of anti-PD1 therapy. In addition, matching tumor biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Here we examined PD-1 and CTLA4 expression in a large and diverse set of samples from CCLE, which provides gene expression data for future experiments, and from TCGA, which provides genomic and survival data that may be useful for clinical investigations. Consistent with previous reports ( 39 , 40 ), we found that PD-1 was more highly expressed in older cancer patients, indicating that checkpoint inhibitor treatment may more effective in this group. Additionally, Black patients had higher PD-1 and CTLA4 levels than Caucasian or Asian patients, suggesting better outcomes following immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Here we examined PD-1 and CTLA4 expression in a large and diverse set of samples from CCLE, which provides gene expression data for future experiments, and from TCGA, which provides genomic and survival data that may be useful for clinical investigations. Consistent with previous reports ( 39 , 40 ), we found that PD-1 was more highly expressed in older cancer patients, indicating that checkpoint inhibitor treatment may more effective in this group. Additionally, Black patients had higher PD-1 and CTLA4 levels than Caucasian or Asian patients, suggesting better outcomes following immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…14 Increased expression of checkpoint inhibitors including TIM3 and PD-1 has also been observed after repeated malaria exposure with increasing age in endemic populations, 62 again with parallels to the emergence of LAG3 and PD1 + adaptive NK cells after activating receptor (NKp30, NKG2D, NKG2C) or HCMV-mediated activation in vitro. 14 Interestingly, a CD25 + CD45RO + NK cell population has been identified in patients with metastatic melanoma treated with anti-PD-1 62,63 further supporting a potential for progressive differentiation of NK cells in a manner analogous to that seen in T cells. There is also evidence that persistent Mycobacterium tuberculosis infections, and the associated chronic inflammatory response, lead to the emergence of CD45RO + NK cells and enrichment of these cells in the pleural effusion fluid of pulmonary tuberculosis patients.…”
Section: Impacts Of Chronic Persistent or Recurrent Infection On Nk mentioning
confidence: 93%
“…As tumor side variables, responders to anti-PD-1 antibody treatment are associated with tumors bearing PD-L1 [ 35 , 36 , 37 ] and MHC-class II [ 38 ]. On the contrary, as a characteristic of host immune cell profiles in responders, a high frequency of CD4 and CD8+ T cells [ 35 , 38 ], NK cells [ 39 ], Th9 [ 40 ], central memory cells [ 41 ], and effector memory T cells [ 42 ] has been observed. IFN-γ is also observed in responders [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%